2016
DOI: 10.1111/hir.12162
|View full text |Cite
|
Sign up to set email alerts
|

A comparative review of gerontological nursing citation data

Abstract: A list of new journal titles is presented to aid collection development and suggestions of places to publish gerontological research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…The growth rate of publications from the third period compared to the previous two periods rose significantly and had a rapid expansion. Antunez and Henry showed that the publication of geriatric nursing articles peaked in 2009 with sixty articles, and the articles received citations nearly 280 times [8]. One of the reasons that publications increased in this period could be that in 2009, several scholars and their colleagues created an alumni organization to use their academic and leadership training for advancing gerontological nursing BioMed Research International [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth rate of publications from the third period compared to the previous two periods rose significantly and had a rapid expansion. Antunez and Henry showed that the publication of geriatric nursing articles peaked in 2009 with sixty articles, and the articles received citations nearly 280 times [8]. One of the reasons that publications increased in this period could be that in 2009, several scholars and their colleagues created an alumni organization to use their academic and leadership training for advancing gerontological nursing BioMed Research International [30].…”
Section: Discussionmentioning
confidence: 99%
“…Geriatric nursing emerged as a specialty after the 1950s. In meeting the needs of the elderly, the need for trained nurses with specialized scientific training to meet the care needs of the elderly was essential [ 8 , 9 ]. This interest was followed by a great desire to conduct scientific research in this field [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aunque este estudio solo evalúo el número de citas bibliográficas, es importante mencionar la existencia de otros indicadores bibliométricos para evaluar el comportamiento de la publicación en la comunidad científica o población en general. Por ejemplo, Antunez et al 20 , mencionan mediciones Pero, a pesar de la existencia de mediciones alternas al conteo de citas bibliográficas, Thelwall 21 menciona que la cuantificación de citas es ampliamente usado para identificar el comportamiento de los artículos y de las revistas. Adicionalmente, es utilizado para fundamentar el juicio de expertos en evaluaciones formales.…”
Section: Discussionunclassified
“…Dichos resultados son relevantes porque permiten apreciar que el consumo de la producción en enfermería se está dando por los mismos profesionales del área, fenómeno que debe ser más investigado. Antunez et al 20 , argumentan que en enfermería deben realizarse más estudios bibliométricos para entender mejor los patrones de citación a través de todos los tipos de literatura y, de tal manera, crear conciencia acerca de la importancia de las investigaciones en esta disciplina en un ambiente competitivo de financiación.…”
Section: Discussionunclassified
“…Since the inception of the Health Information and Libraries Journal review series, we've published an incredible 40 reviews including 11 literature reviews, 11 systematic reviews, five overviews, three comparison review, two state‐of‐the‐art review, a systematic search and review, a systematic review containing bibliometric information, a scoping review, a rapid review, a mixed methods review, a mapping review, a comprehensive review and the typology of review types …”
mentioning
confidence: 99%